Impact of COVID-19 lockdown on physical activity and performance in K-12 physical education: A systematic review - Merino-Campos, Carlos; Del-Castillo, Hector (Journal of Education and e-Learning Research, 2025)
This study explores how the transition to online learning during the COVID-19 lockdown specifically affected the physical performance and activity levels of kindergarten to 12th grade (K-12) students in physical education (PE) classes. This article examines the challenges PE teachers face in maintaining physical activity (PA) engagement remotely and the most effective strategies focusing on a systematic review of the literature published between 2019 and 2023. The study integrates findings from diverse contexts highlighting differences in resources, infrastructure and teacher preparedness. The review highlights specific interventions that successfully mitigated a decline in PA and promoted the physical and mental well-being of students during the pandemic. Among these, structured virtual programs that incorporated innovative technological tools and emphasized family engagement were particularly effective in addressing the decline in physical and mental health indicators. Findings indicate that family participation, easily accessible digital materials, and organized online physical education sessions can be crucial in maintaining students' PA levels. These results underline the importance of tailored strategies to address the unique challenges of online PE and provide evidence for adapting curricula to future crises. This review provides key insights for future applications of online learning in PE with implications for improving student outcomes in physical health during remote learning.